Utilization of Banana (Musa sapientum) Peel for Removal of Pb2+ from Aqueous Solution - Afrida Nurain; Protima Sarker; Md. Mostafizur Rahman; Md. Khabir Uddin; Md. Shiblur Rahaman (Pandawa Institute, 2021)
Biosorption is a convenient process for heavy metal remediation. In this study, banana peel was experimented to eliminate lead (Pb2+) from an aqueous solution following batch experiments. The functional groups of banana peel were identified by Fourier-transform infrared spectroscopy (FTIR). The adsorption mechanism was studied by the Langmuir and Freundlich adsorption isotherm model and determined the separation factor from the Langmuir adsorption isotherm. The adsorption of Pb2+ on dried banana peel had been studied at different adsorbent doses, pH, initial concentration of Pb, contact time, temperature, and agitation speed. After adsorption, Pb2+ was measured using atomic absorption spectroscopy (AAS). Maximum adsorption had taken place at pH 5 for adsorbent dose 45 g L-1. The optimum contact time and agitation speed was 30 minutes and 150 rpm, respectively for the initial Pb concentration of 100 ppm at 25°C. Both, Langmuir and Freundlich adsorption isotherm models shows the best fitting (r2 = 0.9978 and 0.9595) for Pb2+ adsorption. The maximum Pb2+ adsorption capacity was 2.1 mg g-1. The findings indicate that the banana peel waste could be a potential adsorbent for heavy metal removal. Moreover, the waste management problem could be solved in an eco-friendly manner by utilizing it for the eradication of Pb2+ from wastewater.